2010
DOI: 10.1111/j.1365-2648.2010.05450.x
|View full text |Cite
|
Sign up to set email alerts
|

Health Belief Model Scale for Cervical Cancer and Pap Smear Test: psychometric testing

Abstract: The Health Belief Model Scale for Cervical Cancer and the Pap Smear Test was found to be a valid and reliable tool in assessing the women's health beliefs. Understanding the beliefs of women in respect of cervical cancer and the Pap Smear Test will help healthcare professionals to develop more effective cervical cancer screening programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
160
2
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(176 citation statements)
references
References 22 publications
4
160
2
10
Order By: Relevance
“…Pap smear testing is an effective method for detecting, preventing and delaying the progress of cervical cancer (Bebis et al, 2012;Guvenc et al 2011;Getahun et al 2013;Ersin and Bahar, 2013). However, studies in different parts of the world found out that a considerably high percentage of women were unaware of the Pap smear testing (Ak et al, 2010;Bayoumi et al 2011;Farzaneh et al, 2011;Bebis et al, 2012;Senol et al, 2012;Getahun et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pap smear testing is an effective method for detecting, preventing and delaying the progress of cervical cancer (Bebis et al, 2012;Guvenc et al 2011;Getahun et al 2013;Ersin and Bahar, 2013). However, studies in different parts of the world found out that a considerably high percentage of women were unaware of the Pap smear testing (Ak et al, 2010;Bayoumi et al 2011;Farzaneh et al, 2011;Bebis et al, 2012;Senol et al, 2012;Getahun et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Study data were collected by the investigators through a 36-item questionnaire form which was generated using information gathered from similar surveys in literature (Koc and saglam 2009;Ak et al, 2010;Acikgoz et al, 2011;Aydogdu and Bahar, 2011;Guvenc et al, 2011). The questionnaire form included two sections.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological characteristics based on the HBM: regarding psychological characteristics based on the HBM, the survey items were examined based on the preceding studies on cancer screening behaviors (Yarbrough and Braden, 2001;Gozum and Aydin, 2004;Medina-Shepherd and Kleier, 2010;Guvenc et al, 2011;Seki et al, 2011). The questionnaire survey was composed of 7 component based on the revised HBM by Hata et al (2009) (Figure 1).…”
Section: Survey Items and Contentsmentioning
confidence: 99%
“…Later on, selfefficacy was added to HBM to measure the belief in one's own ability to perform a certain behavior [20]. The HBM was originally developed as a systematic method to explain and predict preventive health behaviors and is still one of the most widely used conceptual frameworks of health behavior [21].…”
Section: Introductionmentioning
confidence: 99%